(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
During the period of state terrorism in Argentina, there was a significant intensification of state violence against people with non-heteronormative sexual orientations and/or non-cisnormative gender identities or expressions. In particular, trans women in prostitution were the ones who were most impacted by this escalation of violence. In spite of this, this phenomenon remains lar- gely invisible and scarcely reflected on the trials for crimes against humanity that are taking place in Argentina. This article seeks to highlight what happened to them during those years. It also points to the virtual absence of judicial investigations –within a well-established justice process– regarding the violence they suffered.